2020
DOI: 10.1080/13813455.2020.1792505
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D in pathogenesis and severity of COVID-19 infection

Abstract: Coronavirus disease is an infectious disease caused by a new virus which causes respiratory illness. Older adults and people who have previous chronic medical conditions are at higher risk for more serious complications from COVID-19. Hypovitaminosis D is attributed to the increased risk of lung injury and acute respiratory distress syndrome (ARDS) as well as diabetes, Cardiovascular event and associated comorbidities, which are the main causes of severe clinical problem in COVID-19 patients. Considering the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 61 publications
1
24
0
2
Order By: Relevance
“…In particular, it is known that vitamin D promotes innate immunity processes, e.g., it suppresses adaptive immunity by decreasing the maturation of dendritic cells, diminishing the ability of dendritic cells to present antigen to CD4 cells, suppressing the proliferation of CD4 cells, and their differentiation into Th1 and Th17, and via promotion of Th2 and Treg [85]. Taking into account that vitamin D possesses immunomodulatory and anti-inflammatory properties as well as antiviral effects indicated by numerous studies with well-established data [86], the respective supplementation of patients may support their immune system against COVID-19 [87]. Ilie et al [88] confirmed this using randomized population studies.…”
Section: Food Ingredients and Active Compounds Against Covid-19 Diseasementioning
confidence: 99%
“…In particular, it is known that vitamin D promotes innate immunity processes, e.g., it suppresses adaptive immunity by decreasing the maturation of dendritic cells, diminishing the ability of dendritic cells to present antigen to CD4 cells, suppressing the proliferation of CD4 cells, and their differentiation into Th1 and Th17, and via promotion of Th2 and Treg [85]. Taking into account that vitamin D possesses immunomodulatory and anti-inflammatory properties as well as antiviral effects indicated by numerous studies with well-established data [86], the respective supplementation of patients may support their immune system against COVID-19 [87]. Ilie et al [88] confirmed this using randomized population studies.…”
Section: Food Ingredients and Active Compounds Against Covid-19 Diseasementioning
confidence: 99%
“…On December 31, 2019, several cases with pneumonia of unknown etiology were detected in Wuhan City, Hubei Province of China. Different potential causes such as influenza, avian influenza, adenovirus, severe acute respiratory syndrome coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV) were assessed; however, the pathogen was not identified [1,2]. Consequently, the causative viral disease called COVID-19 by the World Health Organization [1].The recent COVID-19 Situation Report of the World Health Organization reported nearly 32.7 million diagnosed cases with 991,000 deaths around the world until September 27, 2020 [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that vitamin D supplementation might boost the immune system of COVID-19 patients and reduce disease severity in vitamin D deficient patients. [ 10 ] Indeed, bolus vitamin D3 supplementation during or just prior to COVID-19 infection was associated in frail elderly with less severe COVID-19 and better survival rate. [ 11 ].…”
mentioning
confidence: 99%